Information and contemplation: a call for reflection and action. Issue 5 (17th March 2020) - Latham, Kiersten F.; Hartel, Jenna; Gorichanaz, Tim
Abstract : Purpose: Americans increasingly feel a sense of wonder at the universe; meditation and yoga are on the rise; and a field known as Contemplative Studies has emerged. These indicators, among others, suggest a groundswell of interest in contemplative practice and contemplative experience and raise intriguing questions for information and Information Studies. Against this backdrop, this paper asks: How might Information Studies contribute to these developments? What is the relationship between information and contemplation? What can be explored on this research frontier? Design/methodology/approach: This conceptual paper is based upon a synthesis of recent writings from the field of Contemplative Studies as well as conceptual analysis of selected papers and themes in Information Studies. It draws from discussion that occurred at a Session for Interaction and Engagement at the 2018 iConference, entitled "Contemplating Information in the Pleasurable and the Profound" (Latham et al., 2018). The authors' creative thinking and personal contemplative practices also infuse and fortify the work. Findings: Popular and academic contemplative movements are afoot, and Information Studies has an opportunity to participate or be left behind. The field of Contemplative Studies has established the foundational concepts that can serve as contextual material for information research into contemplation. Upon closer inspection, Information Studies has already broached the topic of contemplation at various points in its history, theory, institutional practices, and information behavior research. The conceptual points of departure for a research frontier are articulated. Originality/value: Beyond data, information, and knowledge are deeper and more profound aims, such as wisdom, which is related to contemplation. This paper supplies a rationale, scholarly community, conceptual resources, historical precedents, and guiding questions for bridging information and contemplation.